Increased dietary vitamin D was associated with increased circulating vitamin D with no observable adverse effects in adult dogs - Jewell, Dennis E.; Panickar, Kiran S. (Frontiers in Veterinary Science, 2023)
There is no consensus for the optimum concentration of vitamin D, although a minimum concentration of 100 ng/mL (250 nM) of circulating vitamin D, measured as 25(OH) D, has been suggested in order to support optimal health in dogs. Few studies have examined the relationship between dietary vitamin D3 (cholecalciferol) intake and the resulting concentrations of circulating 25(OH) D in adult dogs. Recommendations for dog foods for adult maintenance report a safe upper limit of 3200 IU vitamin D/kg on a dry matter basis. However, these recommendations were not based on studies of adult maintenance requirements. Understanding the relationship between dietary vitamin D and circulating vitamin D is necessary to utilize dietary vitamin D to influence health in dogs. Methods: Five groups of adult dogs (each n=8) were fed food of approximately 4000 kcal/kg containing one of the following dry matter concentrations of vitamin D for 6 months: 795.7, 3087.3, 5510.9, 7314.0, and 9992.5 IU/kg. Body weight was recorded at baseline and measured weekly, and daily food intake was recorded. Blood samples were taken at baseline and at the end of the 26-week study period. Results: There were no clinical signs of vitamin D deficiency or excess. Serum concentrations of creatinine, blood urea nitrogen, albumin, hematocrit, hemoglobin, alkaline phosphatase, phosphorus, total calcium, ionized calcium, and parathyroid hormone were maintained within reference values in all groups. Circulating 25(OH) D increased in all groups except those that consumed food with 795.7 IU/kg vitamin D, and increased in a linear and quadratic fashion in response to dietary vitamin D concentration. All of the dogs fed food with 5510.9 IU/kg vitamin D or above met or exceeded 100 ng/mL (250 nM) circulating 25(OH) D. Discussion: Dietary vitamin D was positively associated with increased circulating concentrations in concentrations up to 9992.5 IU/kg dry matter, with no observable adverse effects. Consumption of ≥5510.9 IU/kg vitamin D resulted in all dogs with at least the 100 ng/mL (250 nM) circulating concentration.